Iqbal’s Ideal Society and Contemporary Moral Issues - Nisa, Musarrat-Un-; Awan, Muhammad Asif (Makhz (Research Journal), 2025)
Allama Muhammad Iqbal, a visionary philosopher and poet, proposed an ideal society that intertwined spiritual enlightenment, intellectual development and social justice. His concept of an ideal society was based on the foundational principles of self-realization, ethical responsibility and communal harmony. Iqbal’s philosophy emphasized the need for a society where individuals were not only free to pursue personal growth but also committed to the collective well-being of humanity. He championed the ideas of spiritual awakening, unity and social justice, urging that societies thrive when these principles are actively upheld. In the context of contemporary moral issues, Iqbal’s vision offers valuable insights into the ethical challenges faced by modern societies. Issues such as materialism, social inequality and the moral decline in modern times echo Iqbal’s concerns about the imbalance between material pursuits and spiritual fulfillment. His critique of globalization, coupled with the erosion of cultural identities, remains highly relevant in today’s interconnected world. Furthermore, Iqbal’s emphasis on education as a tool for cultivating both intellectual and moral character speaks to the ethical gaps in today’s educational systems where knowledge often overlooks the importance of ethical development. Iqbal’s ideal society, though rooted in timeless values provides a critical framework for addressing the complexities of modern life, advocating for a holistic approach where spiritual, intellectual and moral dimensions of human existence are harmonized for societal progress.